phân tích đa thức thành nhân tử

a)x2+4x+4 b)x2-1 c)x2+2x d)2x2_xy+4x-2y e)3x2-12

user-avatar

a) x2 + 4x + 4 = x2 + 2.2.x + 22 = ( x + 2 )2
b) x2 - 1 = ( x - 1 )( x + 1 )
c) x2 + 2x = x ( x + 2 )
d) 2x2 - xy + 4x - 2y = x ( 2x - y ) + 2( 2x - y ) = ( x + 2 )( 2x - y )
e) 3x2 - 12 = 3( x - 2 )( x + 2 )



user-avatar

a) x2 + 4x + 4 = x2 + 2.2.x + 22 = ( x + 2 )2
b) x2 - 1 = ( x - 1 )( x + 1 )
c) x2 + 2x = x ( x + 2 )
d) 2x2 - xy + 4x - 2y = x ( 2x - y ) + 2( 2x - y ) = ( x + 2 )( 2x - y )
e) 3x2 - 12 =3(x-2)(x+2)




user-avatar

a) x2+4x+4

= x2+4x+2

=(x+2)2

b)x2-1

=x2-12(có thể bỏ bước)

=(x-1)(x+1)

c)x2+2x

=x(x+2)

d)2x2-xy+4x-2y

=(2x2+4x)-(xy+2y)

=2x(x+2)-y(x+2)

=(x+2)(2x-y)

e)3x2-12

=3(x2-22)

=3(x-2)(x+

2)


user-avatar

a)x2+4x+4=x2+2.2.x+22=(x+2)2

b)x2-1=(x-1)(x+1)

c)x2+2x=x(x+2)

d)2x2-xy+4x-2y=(2x2+4x)-(xy+2y)=2x(x+2)+y(x+2)=(2x+y)(x+2)

e)3x2-12=3(x2-4)=3(x2-22)=3(x-2)(x+2)



Các câu hỏi liên quan